Effect of exposure to alpha blockers on cancer-specific and overall mortality in men with prostate cancer: a population-based cohort study. (13th November 2015) - Numbere, Beade; Fleming, Kate Mary; Card, Timothy
Abstract: Background: Prostate cancer is the second most common cause of deaths from cancer in men in the UK, accounting for 13% of male cancer mortality in 2010. Conventional treatment results in cure for some patients but does not prevent the metastasis that occurs frequently in others. Radical new therapies are needed to tackle this cancer progression. Alpha blockers are often given for cardiovascular indications and benign prostatic hyperplasia. In mouse models, they reduce angiogenesis and suppress metastasis. This study aimed to determine the effect of alpha blockers on mortality outcomes in a population-based cohort of men with prostate cancer. Methods: This cohort study used data on 18 654 men with incident prostate cancer from linked UK Clinical Practice Research Datalink, Hospital Episode Statistics, and the National Cancer Intelligence Network between 1998 and 2010. All alpha blocker use in the 6 months after diagnosis of cancer was determined and its effect on all-cause and cancer-specific mortality assessed. Data were analysed with Cox proportional hazards modelling and adjusted for confounding by age, sex, cancer stage, grade, and important comorbidities and coprescriptions. A sensitivity analysis in patients with an indication of hypertension, interaction by dose, and prediagnosis exposure were also considered. Findings: Median follow-up was 4·5 years (IQR 2·2–7·3). Crude mortality rate was 42·2/1000 per year in patients exposed to alpha blockers and 49·6/1000 per year in those unexposed, equivalent to a decreased all-cause mortality (adjusted hazard ratio 0·839, 95% CI 0·776–0·908); crude cancer mortality rate was 20·7/1000 per year and 23·3/1000 per year, respectively, equivalent to a decreased prostate cancer mortality (0·874, 0·781–0·978). In men taking alpha blockers to treat hypertension the effect on all-cause mortality became non-significant (0·857, 0·728–1·217), but a significant decrease in prostate cancer mortality remained (0·692, 0·534–0·897) with a crude cancer mortality rate of 18·5/1000 per year and 27·7/1000 per year in those exposed and unexposed, respectively. No modifying effects were observed by dose and prediagnosis exposure. Interpretation: Alpha blocker use was associated with decreased cancer-specific mortality in men with prostate cancer. Funding: Funding for this project was obtained from the Rosetree Trust, Niger Delta Development Commission (NDDC), and the University of Nottingham. The funders had no involvement in the concept, design, protocol, analysis, or the writing up of this study.